Communities of interest for enhancing social creativity: the case of Womenpower platform - Parmaxi, Antigoni; Vasiliou, Christina (My University, 2015)
Abstract Despite the introduction of gender discrimination and equal legislation, the majority of women still receive lower salaries and status. According to the latest official figuresthe gender pay gap in Europe is 16%. Moreover, women face the so-called glass ceiling effect the invisible, yet unbreachable obstruction that keeps minorities and women from rising to the upper rungs of the corporate ladder, regardless of their qualifications. Thus, in order to develop a modern manifesto for fragmenting this glass ceiling, we endeavor into a community platform that will bring together good practices, successful stories and practical advice on how women can deal with these barriers. This paper discusses Womenpower (WE-ME), a community platform intending to link women mentors and mentees from the fields of academia, technology, business, and health care for promoting women‟s empowerment, equality, and social coherence. Given the nature of this endeavor, there is a need to approach the development as a horizontal process and democratize the design ofthe platform, allowing for different perspectives of stakeholders to be heard and determine the design decisions. Bringing together actors with diverse expertise in the design process encompasses both opportunities and challenges. A basic premise of our approach is that collective communities with diversity of expertise and different approaches to the problem will spark a powerful and dynamic interaction promoting social creativity and building environments that move beyond traditional discipline-bound solutions. In this process, actors with different perspectives undergo a process of mutual ignorance and build on reciprocalteaching and learning for generating new understandings on how a women‟s mentoring platform can be shaped.To this aim, we found Fischer‟s [1]„Communities of interest‟ to be directly relevant. Communities of Interest (CoI) bring together stakeholders with different kinds of expertise to come together for a joint venture.We developed three CoIs:1) a team made up of end users, graphic and software designers. The first CoI wasmediated by computational (mobile devices) and traditional means (paper and pencil) allowing for face-to-face interaction, thus maximizing communication between stakeholders;2) a team made up of end users from the fields of academia, business and technology. The second CoI wasmediated by an interactive tabletop allowing for simultaneous projection, discussion and commenting of the product; and3) a team made up of end users, graphic and software designers. The third CoI operatedwithin a social networking channel allowing for group members to discuss and comment on how the community platform should be constructed. This paper, discusses some examples of how various collectives of professionals came together for addressing a design problem and boost both individual and collective creativity. This study demonstrated that small communities consisting of diverse actors can determine and resolve important design parameters, thus reducing the risk of building a system whichfails to meet users‟ needs. Communities of interest for enhancing social creativity: the case of Womenpower platform. Available from: https://www.researchgate.net/publication/275041375_Communities_of_interest_for_enhancing_social_creativity_the_case_of_Womenpower_platform [accessed May 23, 2016].
Keywords: Communities of interest; Social creativity; Gender equality; Mobile technologies; Tabletop